English Teachers' Readiness to Adopt Educational Technology: Professional Roles and Institutional Support - Fira; Ilham; Rahmaniah, Rima (Universitas Pendidikan Ganesha, 2024)
The world revolution 5.0 has brought major changes in various aspects of life, including education, thus demanding the readiness of teachers, especially English teachers, in adopting educational technology. This study aims to analyze the influence of teachers' professional roles and institutional support on teachers' readiness to adopt educational technology. A quantitative approach was used in this study, with data collection through questionnaires and document studies from 33 respondents. Data were analyzed using multiple linear regression method to identify the relationship between variables. The results showed that teachers' professional roles had a more dominant influence on teachers' readiness, with a regression coefficient of 0.553 and a standardized Beta contribution of 0.765. Meanwhile, institutional support also had a positive, albeit smaller influence with a regression coefficient of 0.220 and a standardized Beta of 0.228. Overall, these two variables explained 85.6% of the variation in teacher readiness. The findings suggest that individual factors, such as teachers' professional roles, have a more significant influence than external factors, although institutional support still plays an important role. This study recommends that local governments and schools develop technology-based training programs to improve teachers' capacity to face educational challenges in the era of the information technology revolution.